BISNIS, LINGKUNGAN HIDUP DAN ETIKA INDUSTRI - Sudiah Hestianah; Dian Mafulla; Dewa Aray Dwiyanto (Dar El-Falah, 2023)
Ethics of carrying out good behavior, namely: social responsibility in theorganizational field, and personal ethics and social ethics. Current globaleconomic growth has given rise to six environmental problems, namely:accumulation of toxic materials, greenhouse effect, destruction of the ozonelayer, acid rain, deforestation and eviction, liver diversity. Ethical principlesin the environment, namely: a) protecting natural ecosystems, b)responsibility, solidarity principles, c) principles of love and care, d)principles of living simply and in harmony with nature, e) protectingecosystems, f) principles of moral integrity. Paradigms for understandingenvironmental ethics: a) ethics of the interests of future generations, b)biocentric environmental ethics, c) ecosystem ethics.